Supply Chain Management Application in Small and Medium Enterprises - Rosy Rochmatullah, Mahameru (ExcelingTech, 2020)
In most emerging markets, small and medium enterprises, (SMEs), lack access to thecredit and liquiditythey require for their dailyworkingcapital needs. Supply chain finance is a broad category of financing with multiple products,and it contributes significantly to global trade finance. This paper utilized several variables, such as changes in liquidity level (quick ratio), changes in debt bias, changes in the cost of goods sold, changes in earnings, and changes in stock returns through the supply chain finance. Employing binary logistic regression, the test results showed that accounts, such as current assets, current debt, long-term debt, net income, cost of goods sold, gross margins, were connected to the agent's opportunistic behavior when the financial health of the company has decreased. In the end, it concluded that SEMs in the management of these accounts was proven by supply chain finance in the preparation of financial statements and good distribution when the financial health of the company has achieved.